Az alföldi külterületi társadalom tagozódása és térbeli rendje 1980-ban - Becsei, József (Tér és Társadalom, 1988)
There are extensive surveys, analyses and debates in social sciences concerning the changes in Hungarian society, its restructuration, but a scientific representation of the spatial aspects of these processes in still missing. The present paper aims at analysing the population living in the outskirts of Alföld settlements from this aspect. (The distinction between inner areas and outskirts or outer areas of settlements is made for planning purposes. The inner area is the built-up, developed area or the territory to be developed; the outer area serves primarily agricultural, recreational etc. purposes. Nevertheless, Hungarian towns and villages, particularly in the Alföld, have people living in the outskirts, often in detached farmsteads. The translator.) Data from the 1980 census were used for these purposes accepting the statistical concept of social structuration. Detached farmsteads represent a specific formation within the Hungarian settlement system. Their developments differ from the overall societal processes in many ways and this divergence has not been adequately dealt with in scientific research. During the past four decades population living in detached farmsteads has significantly decreased. In 1980 only 8.8% of the Alföld population lived in the outskirts. There are extensive areas in the Alföld where there are no more inhabited farmsteads but in other areas (in Bács-Kiskun and Csongrád counties) the number of people living in detached farmsteads is still significant. The social structure of population in the outskirts has markedly changed. The working class has an important (49.3%) representation within the active residents, with an over 50% or dominant percentage in several settlements. In the Alföld the relatíve weight of the other major social class, the collective farm peasantry is smaller than this: 38.1%. The working class is in majority in the outskirts of towns while co-operative peasants live in the outer areas of villages. The age structure and the education level of industrial workers are better than the similar composition indices of those who work in agriculture. Collective farm peasantry is over-represented in the outskirts of tdisadvantaged settlements. Another characteristic feature of outer areas is that they have a larger percentage of small-scale producers within their active residents than inner areas. The analyses made leave us without any doubt over the neccessity of further research, by spatial scientists, into the social changes in the outskirts of settlements.